Palliative care in adult patients with heart failure - Borges, Julia Caetano; Salvador, Victor Sandi Mori (Seven Editora, 2024)
Heart failure (HF) is a chronic and progressive condition in which the heart is unable to pump blood effectively to meet the body’s needs. The disease is one of the main causes of morbidity and mortality in the world. Given its debilitating nature and patients’ compromised quality of life, palliative care plays an essential role in the management of heart failure. This article will cover the key aspects of palliative care for adults with heart failure, including definition, goals, interventions, and the importance of the multidisciplinary team. DOI:https://doi.org/10.56238/sevened2024.025-010